(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
In this brief study, we show how the Database of Semantic Shifts, a large resource on semantic change and semantic motivation, can be represented in Cross-Linguistic Data Formats. The representation allows for a convenient quantitative analysis of the numerous annotations on semantic change and semantic motivation and for the integration of the database with additional resources on semantic change and semantic motivation that have been compiled independently in the last years.